Transcriptome analysis reveals regulatory mechanism of methyl jasmonate-induced monoterpenoid biosynthesis in Mentha arvensis L. - Tingting Huang; Wenjin Men; Ariuntungalag Myanganbayar; Undarmaa Davaasambuu (Frontiers in Plant Science)
Mentha arvensis L. (M. arvensis) is an aromatic plant of the Mentha genus, renowned for its medicinal and economic importance. The primary components of its essential oils (EOs) are monoterpenoids, synthesized and stored in peltate glandular trichomes (PGTs). In general, the EO content in M. arvensis is relatively low. Methyl jasmonate (MJ) has been reported as an effective elicitor of terpenoid biosynthesis in medicinal plants, but the specific mechanisms underlying MJ’s influence on M. arvensis remain unclear. In this study, exogenous application of MJ significantly increased the EO content, yield, and PGT density in a dose-dependent manner. At a 5 mM dose, the EO content and PGT density peaked, with increases of 71.20% and 53.69%, respectively. Gas chromatography-mass spectrometry (GC-MS) analysis indicated that, in general, MJ treatment did not significantly alter the types or relative proportions of EO components of M. arvensis. However, L-menthol content decreased slightly by 7.90% under 5 mM MJ treatment. Transcriptome analysis identified 4,659 differentially expressed genes (DEGs) in MJ-treated leaves. KEGG enrichment analysis revealed that “Monoterpenoid biosynthesis” was among the most significantly enriched metabolic pathways. Key genes involved in jasmonic acid (JA) signaling (JAZs and MYCs) and monoterpenoid biosynthesis (GPPSs, LSs, L3Hs, and IPRs) were significantly up-regulated. Co-expression analysis, promoter binding element analysis and weighted gene co-expression network analysis (WGCNA) indicated that transcription factors (TFs) such as AP2/ERF, WRKY, MYB, and bHLH play crucial roles in regulating MJ-mediated monoterpenoid biosynthesis. Several key candidate TFs potentially involved in regulating monoterpenoid biosynthesis in M. arvensis were identified. These findings provide valuable insights into the molecular mechanisms regulating monoterpenoid accumulation in the Mentha genus.